(untitled) (Revista Eletrônica Debates em Educação Científica e Tecnológica, 2021)
This work aims to discuss the experimentation in science teaching in order to raise questions about the methods used to accomplish these practices in the Science laboratory. The research was conducted with coordinators of schools in the city of Cascavel, PR, where we sought to recognize the understanding of these professionals regarding the relationship between teaching and learning with the Science laboratory. We also conducted a search in scientific articles and books that deal with this topic to understand how researchers understand this theme. We perceive that the use of experimentation is of fundamental importance for the learning of the science content and that the role of the teacher, as a mediator of the teaching and learning process, makes the experimentation meaningful to the student. However, we have seen that some conceptual background problems have been found and need to be reviewed for the efficacy of experimental classes in science teaching.